Effect of dietary biochanin A on lactation performance, antioxidant capacity, rumen fermentation and rumen microbiome of dairy goat - Xu, Qingbiao; Li, Yanjun; Du, Wenjuan; Zheng, Nan; Wang, Jiaqi; Zhao, Shengguo (Frontiers in Microbiology, 2023)
Biochanin A (BCA), an isoflavone phytoestrogen, is a secondary metabolite produced mainly in leguminous plants. The objective of this study was to evaluate the effect of BCA on lactation performance, nitrogen metabolism, and the health of dairy goat. Thirty mid-lactation Saanen dairy goats were divided into three groups randomly: control, 2 g/d BCA group, and 6 g/d BCA group. After 36 days of feeding, 30 dairy goats were transferred to individual metabolic cages. Subsequently, milk yield, feed intake, total feces, and urine excretion were recorded and samples were collected continuously for 3 days. Blood and ruminal fluid samples were collected over the subsequent 4 days. Milk yield, milk protein, fat content, and the feed conversion ratio of dairy goat were significantly increased by the BCA treatment. The levels of serum 17β-estradiol, growth hormone, insulin-like growth factor 1, glutathione peroxidase activity, and total antioxidant capacity were also increased significantly by BCA, indicating that BCA enhanced the antioxidant capacity of dairy goat. Amino acid degradation was significantly inhibited, while the ammonia nitrogen content was reduced significantly by BCA. Total volatile fatty acids was significantly increased by BCA supplementation. In addition, the relative abundance of Verrucomicrobiota was decreased significantly. However, the growth of nitrogen metabolism and cellulolytic bacteria was significantly increased under BCA treatment, including Prevotella sp., Treponema sp., Ruminococcus flavefaciens, and Ruminobacter amylophilus. In conclusion, supplementation with BCA improved the milk production performance, nitrogen metabolism, rumen fermentation and antioxidant capacity, and regulated the rumen microbiome of dairy goat.